2011
DOI: 10.1016/j.ajpath.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Complement 3 and Factor H in Human Cerebrospinal Fluid in Parkinson's Disease, Alzheimer's Disease, and Multiple-System Atrophy

Abstract: Complement activation, a key component of neuroinflammation, has been reported in both Parkinson's disease (PD) and Alzheimer's disease (AD). However, it is unclear whether complement activation and neuroinflammation in general are distinctly different from each another in major neurodegenerative disorders. In the present study, cerebrospinal fluid complement 3 (C3) and factor H (FH) were measured and evaluated together with amyloid-β(42) (Aβ(42)), which in recent investigations was decreased in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 36 publications
8
74
0
Order By: Relevance
“…However, the observed differences were too small to be diagnostically useful. The findings are in line with previous reports showing that a certain isoform of C4b (Finehout et al 2005), C3 and factor H (Wang et al 2011) were elevated in CSF from AD patients.…”
Section: Discussionsupporting
confidence: 94%
“…However, the observed differences were too small to be diagnostically useful. The findings are in line with previous reports showing that a certain isoform of C4b (Finehout et al 2005), C3 and factor H (Wang et al 2011) were elevated in CSF from AD patients.…”
Section: Discussionsupporting
confidence: 94%
“…In the CNS, complement factors C3 and C1q serve not only as mediators of innate immunity, but also coordinate microglial engulfment of supernumerary spines to ensure synaptic refinement and neuronal survival during circuit development (Stevens et al, 2007;Shinjyo et al, 2009;Benoit and Tenner, 2011). In disease, the complement system is strongly activated by neuronal damage, consistent with the observation of prominent complement protein expression in response to A␤ exposure and in AD brain tissue (Bradt et al, 1998;Tacnet-Delorme et al, 2001;Fan and Tenner, 2004;Loeffler et al, 2008;Wang et al, 2011). The identification of complement receptor 1 as a genetic risk factor in AD (Lambert et al, 2009;Crehan et al, 2012) raises the possibility that complement activation may be an active participant in AD pathogenesis rather than a passive consequence of amyloid deposition.…”
Section: Introductionsupporting
confidence: 53%
“…those from DJ-1), even though they were included in the list, failed to pass our rigorous pipeline selection criteria. That said, a peptide from complement factor C3 (C3), a potential marker identified in CSF in our previous study (58), did appear as one of the 17 peptides identified in the training set. In further investigations, we will try to optimize the conditions to include not only these robust biomarker candidates but also known potential markers such as ␣-synuclein and DJ-1 for an "ideal" panel of markers to be used clinically.…”
Section: Discussionmentioning
confidence: 99%